Characteristics of the composition of an administrative offense related to violation of the rules of quarantine of people - M. I. Martsun (Bulletin of Kharkiv National University of Internal Affairs)
The research is devoted to the study of the composition of an administrative offense related to violations of the rules of quarantine of people. The general, generic, and direct objects of administrative offense are defined. The general object of an administrative offense under Art. 44-3 of the Code of Administrative Offenses is the order of public administration, the generic object is public relations in health care, and the direct one is the health of the individual.